Lama Terapi Jus Semangka Terhadap Tekanan Darah Lansia Penderita Hipertensi - erwin kurniasih (STIKES Bhakti Husada Mulia Madiun, 2020)
Hypertension is a condition of systolic pressure above 140 mmHg and diastolic above 90 mmHg. Hypertension is more prevalent in elderly people aged 55 years and over, as we age, blood pressure increases. Hypertension can cause complications including heart damage, stroke, kidney failure. Non-pharmacological therapy to reduce blood pressure is one of them by using watermelon which has potassium content in helping the heart work and normalizes blood pressure. The purpose of this study was to analyze the differences in the effectiveness of the administration of watermelon juice for 5 days and 7 days against changes in blood pressure in elderly people with hypertension. The study used the True Experimental method with Randomized Pre-Post Test Design. The sampling technique uses Simple Random Sampling with the number of respondents as many as 36 elderly people divided into two treatment groups. The results of the Wilcoxcon test for administration of watermelon juice for 5 days obtained p = 0,000 (0.05) and the watermelon juice supply for 7 days obtained p = 0,000 (0.05), meaning that there was a change in blood pressure before and after watermelon juice administration watermelon juice for 5 days and 7 days. The results of the Mann-Whitney test comparing the two groups obtained systolic values p = 0.490 ( 0.05) and diastolic p = 0.732 ( 0.05) meaning that there was no difference in the effectiveness of the watermelon juice for 5 days and 7 days for changes in blood pressure. Based on the results of the analysis there was no difference in the long-term effectiveness of giving watermelon juice for 5 days and 7 days to changes in blood pressure in elderly people with hypertension. This therapy is equally effective in lowering blood pressure, so that more effective consumption of watermelon juice for 5 days has been able to reduce blood pressure.